A rectal duplication cyst with rectovaginal fistula: A case report - Usama Qumsieh; Insaf Abdelghani; Weaam Omran; Fatima Manasra; Nancy Ahmad; Bara'a Shawar (Elsevier, 2022)
Background: Alimentary tract duplications (ATD's) are rare congenital anatomical abnormalities. They have an incidence of 1 in 4500 live births and can occur anywhere throughout the digestive tract from the oropharynx to the anus.ATD's occurs most commonly in the midgut (56%), less commonly in the foregut (33%) and even more rare in the hind gut (11%).Rectal duplications are the least common among other alimentary tract duplications, forming only 4% of them. Typically, they are cystic masses, slightly more common in males and they can present in the newborns period or any time later in childhood and even adulthood. Case presentation: We describe a case of an adolescent female presenting with long standing constipation since birth associated with painful defecation and offensive stool odor, abdominal pain and distention. She recently noticed stool in the vagina at the time of defecation.Patient was admitted to our medical center for further investigations and underwent colonoscopy. The study showed two pouches in the rectum, one with blind end and ulcer with suspected fistula opening, and the other lumen continues to the cecum.Abdomen and pelvic CT with rectal contrast was also done, showing a huge recto-sigmoid duplication cyst compressing the native rectum. Evidence of contrast in the vagina was also seen.Decision for surgery was then made. The procedure commenced laparoscopically, showing a huge duplication cyst starting at the distal part of sigmoid and extending downward distally to the rectum. Severe adhesions and edema was also encountered (frozen pelvis) which forced us to convert to open surgery.It was not possible therefore, to perform complete excision of the cyst without risking to damage the rectum and surrounding structures, which will increase the morbidity significantly in our case. Moreover, the fistula was not seen from this approach, as it was very low.We eventually performed a near total cystectomy with the sigmoid attached to it, joined the common wall of the remaining of the cyst and the native rectosigmoid using endo-GIA staplers. We decided to exteriorize the proximal colon as end colostomy.Subsequently, the fistula was taken down trans-vaginally by the gynecology team as a second procedure .A third procedure was performed 6 months later, a laparotomy was performed, the colostomy was taken down and primary anastomosis was performed.No immediate postoperative complications were seen and the patient was discharged in good general condition. Conclusion: This is a unique case as it is a case of a huge rectosigmoidal duplication cyst that was discovered in a female at an adolescent age, causing severe adhesions and chronic inflammations in the pelvis which led to a rectovaginal fistula and made complete resection impossible without converting the surgery into a major surgery with risk of morbidity and long term sequela.As the condition is considered benign, the medical literature is usually against performing a major surgery that can be harmful to the patient like a very low anterior resection to excise the duplication cyst as it is acceptable to perform partial excision with unification the two lumens together which was performed in our case.This case is an example of multistage and multidisciplinary procedure to treat a rare duplication cyst anomaly.